Implementasi Kurikulum Merdeka pada Pembelajaran Pendidikan Agama Islam (PAI) di Sekolah Dasar Tahfidz Quran (SDTQ) As-Surkati Salatiga - Arif Gunawan Santoso (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2025)
This study aims to describe how the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) learning at the primary school level, especially in elementary schools based on Tahfidzul Quran. This research uses an instrumental case study approach with SDTQ As-Surkati as the research subject. Data and information are extracted through interviews, document study, and observation of the implementation of the Merdeka Curriculum. The data and information obtained were analyzed using the POAC approach (Planning, Organizing, Actuating, and Controlling) approach. The analysis focused on underlying aspects of the institution’s decisions, processes and problems, also how the actors involved contributed to the implementation of the Merdeka Curriculum. Based on the analysis, it was found that SDTQ As-Surkati took the initiative to implement the Merdeka Curriculum in the school year 2022/2023. The initiative was based on the school's ability to adapt more quickly to the Merdeka Curriculum. In terms of PAI learning, the school uses the Merdeka Curriculum adapted to its needs. PAI lessons at SDTQ As-Surkati are divided into four sub-lessons, which are taught using the student-centred approach of the Merdeka Curriculum. Some sub-lessons are organised by prioritising the set objectives and orientations. The challenges encountered in implementing the Merdeka Curriculum in PAI (Islamic Education) learning include the provision of facilities and infrastructure as well as the limited allocation of learning time.